2004
DOI: 10.1093/ilar.45.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Gottingen Minipig as a Model of Diabetes, with Special Focus on Type 1 Diabetes Research

Abstract: Animal models of type 1 diabetes remain essential tools for investigation of the etiology and pathogenesis of the disease and, importantly, for the development of effective new treatments. Although a range of well-characterized and widely used models of type 1 diabetes in rodents are currently available, large animal models are a valuable complement to rodent models for both physiological and practical reasons. The pig is very useful in many aspects as a model for human physiology and pathophysiology because m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 143 publications
4
117
1
2
Order By: Relevance
“…Miniature pigs continue to elicit interest as an animal model in the fields of biomedical research [12], transplantation organs [13,14] and disease models [15,16]. However, lack of comprehensive studies on miniature pigs and their cloning has made cloning in them less efficient than in other animals, including domestic pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Miniature pigs continue to elicit interest as an animal model in the fields of biomedical research [12], transplantation organs [13,14] and disease models [15,16]. However, lack of comprehensive studies on miniature pigs and their cloning has made cloning in them less efficient than in other animals, including domestic pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional areas (mm 2 ) of approximately 200 muscle fibres were measured with an MOP digiplan analyzer (Kontron, Messgeräte GmbH) on photographs of myofibrillar ATPase-stained ( pH 4.6) transverse sections. 20 The insulin content of biopsy samples from the liver and pancreas was determined by extracting insulin by mixing homogenates with acid-ethanol (0.18 mmol/L HCl in 96% ethanol) overnight at 48C.…”
Section: Tissue Analysesmentioning
confidence: 99%
“…Although rat preadipocytes and http://bmbreports.org BMB reports adipocytes lines are commonly used in obesity studies, it has been suggested that porcine preadipocytes are a better model for the study of obesity and its related disorders because porcine preadipocytes possess higher lipogenic capacity and similar lipogenic patterns to human adipocytes (21)(22)(23). Fernandez reported that guinea pigs could be used as models to study hepatic cholesterol and lipoprotein metabolism (24).…”
Section: Introductionmentioning
confidence: 99%